Comparative Histological Study of Dentinopulpal Responses in Class I Cavity Treated by Er: YAG Laser and Conventional Cavity Preparations: An in Vivo Trial - Al-Gazali, Maha W.; Mahmood, Ali S.; Al-Azzawi, Lehadh M.; Jarjess, Rayid K. (Iraqi Journal of Laser, 2010)
The purpose of this study is to investigate the histopathological response of dentinopulpal response of human teeth to the Er: YAG laser cavity preparation in comparison with the conventional class I cavity preparation. Thirty five sound human upper and lower first premolar teeth which were needed to be extracted for orthodontic purposes were used in the study. Regarding to the method of cavity preparation, the teeth were grouped into three groups; Group1; Control group which consists of seven sound teeth without cavity preparation, Group2; Conventional cavity preparation group and group 3; Er: YAG laser cavity preparation group. Each of Group2 and3 consists of fourteen teeth that is subdivided into: A. 7teeth that extracted after two days after cavity preparation and B. 7 teeth that extracted after twenty-one days after cavity preparation. Er: YAG Laser device emits radiation at wavelength of 2940 nm in the infrared region. The laser irradiation was performed in a non-contact mode with a focused beam of (energy density of 155985.96 mJ /cm2, energy of 600 mJ and a PRRs of 6 Hz for enamel preparation) and (energy density=64994.151 mJ /cm2, energy = 250 mJ and a PRRs=4 Hz for dentin preparation) with a spot diameter of 0.7mm at 12-15 mm distance and at right angle to the tooth surface as possible. The histopathological results of the cavities prepared by Er: YAG Laser revealed the early proliferation of the odontoblasts in the odontoblastic layer of the coronal part of the pulp which led to the early formation of the reparative dentin in comparison to those prepared by conventional method. It can be concluded that the use of the Er: YAG laser in class I cavity preparation has proved to be an efficient technique in comparison to the conventional cavity preparation.